2009
DOI: 10.1016/j.amjcard.2008.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Inflammation to Depression and Incident Coronary Heart Disease (from the Canadian Nova Scotia Health Survey [NSHS95] Prospective Population Study)

Abstract: Numerous studies have found that depression is a strong independent risk factor for incident coronary heart disease (CHD), with increasing risk among those with higher levels of depressive symptoms. We examined the association between measures of inflammation (C-reactive protein, interleukin-6, soluble intracellular adhesion molecule-1), depressive symptoms, and CHD incidence among 1,794 participants of the population-based Canadian Nova Scotia Health Survey. There were 152 (8.5%) incident CHD events (141 nonf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 32 publications
6
59
1
Order By: Relevance
“…It might also be particularly helpful when searching for potential mediating factors that could ultimately be targeted in prevention strategies. 21,22 From a clinical perspective, the present results urge clinicians to consider depressive symptoms as a cardiovascular risk factor on their own when experienced by individuals of low occupational grade. Therefore, in addition to the management of more traditional risk factors, depressive symptoms could represent a specific target for cardiovascular preventive intervention among these individuals in a personalized medicine approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might also be particularly helpful when searching for potential mediating factors that could ultimately be targeted in prevention strategies. 21,22 From a clinical perspective, the present results urge clinicians to consider depressive symptoms as a cardiovascular risk factor on their own when experienced by individuals of low occupational grade. Therefore, in addition to the management of more traditional risk factors, depressive symptoms could represent a specific target for cardiovascular preventive intervention among these individuals in a personalized medicine approach.…”
Section: Discussionmentioning
confidence: 99%
“…20 More direct, biological pathways, including imbalanced sympathetic-parasympathetic activity or chronic low-grade inflammation, are also hypothesized although evidence for their actual mediating role is weak. 21,22 Finally, subclinical vascular brain damages leading to poor emotion regulation might partially confound the association. 23 Likewise, several mechanisms may explain social inequalities in cardiovascular health.…”
Section: Explanatory Hypothesesmentioning
confidence: 99%
“…The theory of inflammation as a link between psychological stress and CAD has become a rather well-established fact over the years (177,178), even if this theory has been questioned lately. Some large prospective studies showing that psychological distress, such as depressivity and negative affect, predict risk of future CAD events, show that the risk remains after adjustment for the inflammatory markers CRP and IL-6 (98,179,180). Similarly, the inflammatory markers predict the incidence of CAD, but independently of the psychological factors.…”
Section: Exploring the Potential Associations Between Pbmcderived Levmentioning
confidence: 99%
“…Several other clinical trials [50,52,58,59,61] have inferred that there is a significant linkage between depression and inflammatory markers such as CRP, IL-6, and intercellular adhesion molecule-1 (ICAM-1). Nevertheless, the majority of them have concluded that inflammation accounts for only a small percentage of the cardiotoxic effect and the incidence of CHD of depression, indicating that multiple mechanisms are involved.…”
Section: Depressionmentioning
confidence: 99%